EVALUATION OF BREAD WHEAT GENOTYPES USING SELECTION INDEX - HUSSAIN, MOHAMMED ALI; SAEED, REZGAR IDREES; ASKANDAR , HAJER S.A.; KHETHER , ABBAS ALO (Journal of Duhok University, 2020)
Experiment was carried out at farm of Field Crop Department, College of Agriculture, University of Duhok.  Twelve genotypes of bread wheat were sowing in 25/11/2017 to construct selection indices using Randomize Complete Block Design (RCBD) with three replications.The experiment included six traits studied were plant height (cm), flag leaf area (cm2), No. of grains spike-1, weight of seed spike-1,1000-grain weight (gm) and grain yield row-1 (gm). The results showed the analysis of variance for six traits was highly significant for plant height, No. of grain spike-1, weight of grains spike, 1000-grain weight and non-significant for flag leaf area. Although the results revealed the combined analysis were highly significant difference for all traits except No. of grain spike-1 and weight of grain spike-1. Also, the results exhibited the best selection index was (L146) which include the traits (grain yield, plant height, 1000-grain weight) and giving relative efficiency 7-29%. Of selection of yield alone. The GCV was medium for all traits and low for flag leaf area while, the PCV was medium for plant height, weight grain   spike -1, No. of grain spike-1 and 1000-grain weight, whereas, high for grain yield and low for flag leaf area. Concurring the genetic advance as mean (GAM) the results showed the high value for number of grain spike-1 and weight of grain spike-1 and medium for plant height, 1000-grain weight, grain yield and low for flag leaf area, the value ranged between 5.07 to 20.47%. The heritability was high for all traits and medium for flag leaf area. The results indicated highly significant difference between the wheat genotype in the value of selection index for these which computed depend on the better selection index, grain yield, plant height and 1000-grain weight.Form this study that the better for genotypes was Abu- graib-1, Research-4, IPA-99 and Sham-6, over all genotypes and could be used this genotypes in breeding program to improve yield of wheat and develop new variety with good productivity and good quality performance to Kurdistan and Iraqi environments